Black Phosphorus: Avalanche Carrier Multiplication in Multilayer Black Phosphorus and Avalanche Photodetector (Small 38/2019). Issue 38 (18th September 2019) - Jia, Jingyuan; Jeon, Jaeho; Park, Jin‐Hong; Lee, Byoung Hun; Hwang, Euyheon; Lee, Sungjoo
Abstract : In article number1805352, Euyheon Hwang, Sungjoo Lee, and co‐workers demonstrate black phosphorus‐based avalanche photodetectors integrated with Au‐nanoparticles. By exploiting a strong avalanche multiplication of electron–hole pairs at low electric field, significantly enhanced sensitivity and gains are achieved for application in low‐power‐consumption, high‐sensitivity, and low‐noise optical communication and imaging systems.